A Modified Kole's Osteotomy for Correction of Anterior Open Bite and Macrogenia in a Cleft Patient. Issue 1 (March 2013) - Ramanathan, Manikandhan; Rao, Srinivasan H.
We present a modified technique to close anterior open bite as well as to correct anterior and vertical macrogenia without sacrificing the lowermost symphyseal segment, in comparison with conventional Kole's osteotomy, which can alter the symmetric bone architecture of the chin and jeopardize the blood supply of the sandwich segments.